Avaliação da adsorção do herbicida diuronutilizando carvão ativado granular em solução sintéticacontaminada - Wandembruck, Mariane Tavares (2015)
Diuron is a common herbicid used to control the growth of grass-weed among sugar cane plantation. By having to high toxicity and present a moderate to high capacity to persist in the environment, this herbicide has contributed to the increasing environmental contamination being found for many years in different types of national and international soils and waters. For this reason, this herbicid may be removed by different techniques that ensure an efficient elimination of it. The aim of this study was to evaluate diuron's removal by a synthetic solution of activated charcoal of babassu coconut (CAGCB). This activated carbon was used in natura featured to zero load point (PCZ) With value of 7,88 and to specific area (BET) of 5 l7,4 m2 g'1 with predominantly microporous structure. The adsorption testes were made in batch and duplicated. The pH was around 6 (natural pH of the solution) in the determination of kinetic and isothermal adsorption tests. For the adsorption kinetic test, it was used a diuron's initial concentration (CQ) of 25,72mg L'l, pH around 6, from a granular activated charcoal of babassu coconut dosis of 0,4g L" under stirring speed of 200 rpm and ambient temperature (25 °C). The result expressed a diuron's experimental adsorbed amount of 34,40lmg g1 that Was achieved in a period of 5 hours, corresponding to equilibrium time. Experimental data show a sinusoidal behavior manly due to the presence of macropores on the granular activated charcoal of babassu coconut surface that limited the access of diuron's molecules in its microporos, since these molecules are larger in size than the size of these microporous contributing to block these pores. About the two kinetic models evaluated in this study, the pseudo-second order model fitted a little better experimental data, achieved a correlation coefficient of 0,8 and removed a greater amount of diuron (41,586 mg g'1) when compared to the pseudo-first order model. These results, according to literature, indicate that adsorption occurs through a chemical nature mechanism (chemisorption). Adsorption isotherms were performed by maintaining contact 25 mL of a sinthetic solution contaminated by diuron in a initial concentration of 23,77 mg Lil, at pH around 6 with a mass change of the granular activated carbon of babassu coconut between 0.01 and 0,055 g, under stirring speed of 200 rpm and three different temperatures (25°C, 35°C and 45°C). Results show that Langmuir model adjusted better to the lowest temperature which indicates that the reached isotherm was favorable and a diuron's monolayer was formed on the adsorbent surface (CAGCB). The other temperatures exhibit a better fit to the Freundlich model which indicated that there were multilayer on the adsorbent surface. Out of the three temperatures that were evaluated, 45°C was the one that showed best adsorption capacity with 54,286mg g'1. Finally, thermodynamic parameters were calculated for the three temperatures reaching a system with spontaneous, favorable, endothermic process and increased disorder. The system's enthalpy high and positive value (48,23 ]mol") indicated that the adsorption process was due to chemisorption, which confirms the model of pseudo-second order is the most favorable for the adsorption process.